Brand Equity Model for Print Media Outlets in a Regional Context [Modelo de Valor de Marca Para Meios de Imprensa Escritos Num Contexto Regional] [Modelo de Valor de Marca Para Medios de Prensa Escritos en Un Contexto Regional] - Aguirre-Gonzalez, M (Universidad Icesi, 2015)
The aim of the present study is to propose a scale that enables brand equity for print media outlets to be measured. For this, a three-step process was developed, consisting of: the development of a scale with validity of content; the application of a pre-quantitative test to the scale constructed and, finally, the data collection with the improved scale, and the analysis of the psychometric properties of this scale. The assessment of the psychometric properties included a confirmatory factor analysis of the structural equation modeling that represents the measurement scale. The six resulting explanatory dimensions are: affective-behavioral loyalty, cognitive loyalty, brand associations, perceived quality, brand recognition and brand recall. © 2015 Universidad ICESI. Published by Elsevier España, S.L.U. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).